Dissociative electron attachment dynamics of ozone using velocity slice imaging. (August 2015) - Gope, Krishnendu; Prabhudesai, Vaibhav S; Mason, Nigel; Krishnakumar, E
Synopsis: We report the study of dissociative electron attachment to ozone (O3 ) in the energy range of 1 to 10 eV using velocity slice imaging technique. Based on the momentum images that we obtained for O − and O2 − channels at various electron energies we unravel the molecular dynamics leading to DEA.